The financial education : part of corporate social responsibility for employees and customers - Corina Ene; Mirela Panait (Revista română de economie, 2017)
Nowadays, some categories of the population tend to become economically vulnerable because of a complex set of factors, which include insufficient financial education. The paper consists in an analysis on the importance of financial education as a tool for reducing the vulnerability of the population, detailing key components of this component of corporate social responsibility and highlighting the efforts made on this issue at international level and in Romania. On the one hand, the companies develop financial education programs for employees so that they reach a certain level of wealth and to be able to provide a decent living even after retirement. On the other hand, other categories of financial education programs targeted are banks` clients (customers) and potential portfolio investors on the stock market. The article also highlights the relevance of financial education in the broader context of the Romanian consumer protection, drawing a few lines of action required in this area. From the results recorded internationally on financial education for certain categories of stakeholders, the authors propose and analyze the specific situation of the Romanian economy. In our country, the main promoters of financial education are banks which conduct various social responsibility programs to familiarize the population with specialized terms, raising awareness of customers about the risks posed by credit products offered by financial institutions. Efforts should be intensified and concerted by banks considering that in our country, about half of the population is not banked and a quarter is considered to be over-indebted. Financial education to familiarize the population with banking products must completed taking in to account the other components of the financial market - namely capital market and insurance market, so people are able to invest the savings available for financial gain during active life and to achieve a certain level of financial stability so necessary after retirement.
2665773-9; 2344-4657; Revista română de economie; 717197875